DIGITAL RECONSTRUCTOR: INTEGRATION OF DIGITAL TWINS FOR THE RECONSTRUCTION AND REMEDIATION OF WAR-AFFECTED TERRITORIES IN UKRAINE (UKLO Proceedings, 2025)
This article provides a comprehensive analysis of the potential and opportunities of Digital Twin technology for the reconstruction and remediation of socio-economic and ecological systems in Ukraine. Given the scale of destruction caused by military activities, limited resources, and tight recovery timelines, traditional remediation methods often prove too slow and resource-intensive. To address this, the authors propose a project aimed at implementing Digital Twin systems for the integrated restoration of infrastructure in these systems. Virtual models of war-damaged infrastructure (roads, bridges, buildings) and ecosystems (forests, water systems) will be created using geospatial data, sensors, and real-time monitoring technologies, enabling timely responses, effective decision-making, and efficient resource management. The study examines successful applications of Digital Twins and discusses their challenges and prospects within sustainable development. The results confirm that the adoption of Digital Twin technology can significantly enhance post-war recovery efforts. The authors’ future research will focus on successful digital transformation experiences and the development of frameworks to optimize the integration of Digital Twins into Ukraine’s post-war remediation management model.